Design A Simple Solar Tracker For Hybrid Power Supply - Kamarudin, Muhammad Nizam; Rizman, Z.I.; Ishak, M.T.; Hashim, F.R.; Yassin, Ihsan M.; Zabidi, A.; Zaman, F.K.; K., H. Yeap (faculty of sciences and technology of the University of El Oued (Algeria), 2018)
This paper presents a smart power supply by using solar energy as the sources.It reduces the use of fuel in order to achieve maximize generation of electricity (during day time).The project equipped with solar tracker device which is absorbs the ultraviolet (UV) from the sun in maximum condition.The tracker operates with dual axis rotation where it can be rotating with 360° or which is 180° vertical/horizontals.This circuit is activated when light dependent resistor (LDR) detecting the light where four sensors are placed at east,west,north and south position.The solar panel is embedded with gear system to control the speed of the tracker and also obtain full charge of the 12V rechargeable lead acid battery.